KONSEP MULTIKULTURAL, MULTIKULTURALISME DI INDONESIA, PENDIDIKAN KARAKTER - Mulyadi Mulyadi (Jurnal Manajemen Pendidikan, 2026)
Indonesia is a country with a very high level of diversity, including differences in ethnicity, culture, language, religion and tradition, making it the largest multicultural laboratory in the world. This condition is both a strength and a challenge in maintaining national integration and unity, especially in the midst of globalization and the increasing potential for social conflicts based on differences. This article aims to analyze the concepts of multiculturalism and multiculturalism, examine the dynamics of multiculturalism in Indonesia, and identify the role of character education in strengthening multicultural values. The study method used is library research by examining various scientific sources in the form of books, journal articles, and relevant policy documents, then analyzed descriptively-qualitatively. The results show that multiculturalism is a normative view that emphasizes recognition, appreciation, and management of diversity as a social force. Multicultural-based character education plays an important role in fostering tolerance, empathy, and mutual respect through the development of cultural, societal, and personality competencies. The implications of this study confirm that strengthening multicultural-based character education in an integrative, compact, and consistent manner in educational institutions is an important strategy to prevent national disintegration and realize an inclusive, democratic, and socially just Indonesian society.